JARINGAN KOMUNIKASI, MODAL SOSIAL DAN ENERGI SOSIAL BUDAYA KREATIF DALAM MENGEMBANGKAN KELEMBAGAAN PETERNAKAN, SEBUAH TINJAUAN TEORITIS - Muh. Zainal S. (Universitas Muhammadiyah Jakarta, 2018)
Efforts to build cooperation that is born from local wisdom values of a society that aims to overcome the problems for example in the aspect of livestock business activity is a component of social capital and social energy that must be developed and maintained in order to achieve empowerment and independence. These efforts require communication networks both within and outside the group. Through the communication network occurs the process of communication to share messages or information, especially related to livestock farming. Communication networks, social capital and social energy of creative culture have an important role in developing a community institution that is expected to lead to the realization of empowerment and independence. This article aims to produce the theoretical descriptions of communication networks, social capital, institutions, and creative social and cultural energies. The method of writing this article using a qualitative approach using literature study (desk study) is by collecting relevant literature. Keywords: communication network, energy of creative cultural social, social capital